Phosphorus metabolic disorder of Guizhou semi-fine wool sheep. - Xiaoyun Shen; Jinhua Zhang; Renduo Zhang (PLoS ONE)
Guizhou semi-fine wool sheep are affected by a disease, characterized by emaciation, lameness, stiffness in the gait, enlargement of the costochondral junctions, and abnormal curvature in the long bones. The objective of this study was to determine possible relationships between the disease and mineral deficiencies. Samples of tissue and blood were collected from affected and unaffected sheep. Samples of soil and forage were collected from affected and unaffected areas. The samples were used for biochemical analyses and mineral nutrient measurements. Results showed that phosphorus (P) concentrations in forage samples from affected areas were significantly lower than those from unaffected areas (P < 0.01) and the mean ratio of calcium (Ca) to P in the affected forage was 12:1. Meanwhile, P concentrations of blood, bone, tooth, and wool from the affected sheep were also significantly lower than those from the unaffected group (P < 0.01). Serum P levels of the affected animals were much lower than those of the unaffected ones, whereas serum alkaline phosphatase levels from the affected were significantly higher than those from the unaffected (P < 0.01). Inorganic P levels of the affected sheep were about half of those in the control group. Oral administration of disodium hydrogen phosphate prevented and cured the disease. The study clearly demonstrated that the disease of Guizhou semi-fine wool sheep was mainly caused by the P deficiency in forage, as a result of fenced pasture and animal habitat fragmentation.